THE EFFECT OF PROBLEM-BASED LEARNING ON EFL STUDENTS' ACHIEVEMENT AND CRITICAL THINKING SKILLS: AN EXPERIMENTAL STUDY - Sayfadin Ibrahim Sharif (Guruku)
This experimental study investigates the impact of Problem-Based Learning (PBL) Apost-test). Statistical analyses, including independent and paired samples t-tests as well as a Two-Way ANOVA, revealed that the experimental group significantly outperformed the control group in academic achievement, with a large effect size (η² = 0.21). Additionally, female students in the experimental group exhibited higher achievement scores compared to their male counterparts; however, the interaction between teaching method and gender was not statistically significant. These findings underscore the potential of PBL to enhance both academic outcomes and critical thinking abilities in EFL contexts, suggesting that active, student-centered instructional strategies may offer substantial benefits over traditional teaching methods.